Dynamics of uncoupled and coupled neurons under an external pulsed current. (February 2022) - Hansen, Matheus; Protachevicz, Paulo R.; Iarosz, Kelly C.; Caldas, Iberê L.; Batista, Antonio M.; Macau, Elbert E.N.
Highlights: We focus on the study of the neuronal activities and identification of syn- chronous patterns in uncoupled and coupled excitatory HH neurons. These neurons are stimulated by an external current which has a constant or pulsed profile. Random pulses may introduce an uncertainty about the ranges of the bistable states, as well as in the synchronous and desynchronous patterns. Small intervals of random pulses embedded in a sequence of periodic pulses can be enough to generate uncertainty not only in the neuronal activities, but also in the synchronous behaviour. Abstract: The neuron dynamics is highly susceptible to variations in its current input. In this work, we study the dynamics of uncoupled and random coupled Hodgkin Huxley neurons under an external current with constant or pulsed amplitude. The profile of these pulse perturbations are considered as periodic, random, and a mix between these two types. For uncoupled and coupled neurons submitted to a constant input current, we observe neuronal silence, spike, and coexistence between these two regimes, as well as spike synchronisation. However, when periodic pulse perturbations are introduced, the neuronal activities depend on the pulse parameters, as the amplitude and duration values. For random pulsed inputs, the complexity is greater, once such perturbation may induce the appearance of uncertainty in the neuronal dynamics. Furthermore, our simulations suggest that small time windows, in which the random pulses are embedded in a sequence of periodic pulses, are already enough to bring uncertainty in the neuronal activities. In such a scenario, the excitatory couplings can reduce these uncertainties around the behaviour developed by the neurons.